GENOTYPE SEEDLING AGE INTERACTION FOR HYBRID SEED YIELD OF RICE (Oryza sativa L.) - Islam, M. Ariful; Sarker, U. K.; Mian, M. A. K.; Ahmed, J. U. (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The experiment was carried out in Randomized Completely Block Design (RCBD) during the Boro season 2006-2007 (Mid October to mid May) at Bangabandhu Sheikh Mujibur Rahaman Agricultural University-Gazipur. Alok showed significant bi but its deviation from regression (S2di) invalided its linear prediction. Among the three CMS lines CMS-2 was stable for % OCR due to considerable mean, phenotypic index, regression coefficient near unity (bi ? 1) as well as insignificant deviation from regression (S2di ? 0) and CMS-1 was highly responsive to seedling ages due to significant bi and insignificant S2di. Although, Alok showed significant bi but its deviation from regression (S2di) invalided its linear prediction. Maximum out crossing rate was obtained from CMS-2 irrespective of seedling ages. On the other hand 43 days old seedling of CMS-1 gave the maximum out crossing rate. CMS-2 was highly responsive to yield over seedling ages. CMS-1 showed insignificant regression coefficient (bi) indicating stability over seedling ages but deviation from regression (S2di) was significant which invalided its linear prediction. Alok showed lower mean, significant regression coefficient (bi) and insignificant deviation from regression (S2di) indicating responsitive to favourable seedling ages with comparatively lower yield. 43 days old seedlings of CMS-2 gave the maximum hybrid seed production rate. DOI: http://dx.doi.org/10.3329/bjpbg.v24i1.16995